Access 2003 VBA Programmer's Reference - Cardoza, Patricia; Hennig, Teresa; Seach, Graham; Stein, Armen (John Wiley & Sons, Incorporated, 2004)
Its power and short learning curve have made Access Microsoft's leading consumer relational database management system for desktop applications. VBA lets you tap more of that power, responding to application level events, displaying forms and reports, manipulating toolbars, and much more. In this book, a crack team of programmers including two Microsoft MVPs shows you how to take control of Access 2003 or 2002 using VBA. You'll learn to create and name variables, use DAO and ADO to manipulate data, handle errors correctly, create classes and use APIs, and more. An entire chapter is devoted to the changes in Access 2003, including new wizards and GUI features that previously required VBA code as well as new VBA features. You'll receive a thorough education in system security, macro security, and the Access Developer Extensions (ADE). You will discover how to access data with VBA, execute and debug VBA code, and use VBA with Access objects. Finally, you will learn more about the relationship between Access and SQL Server®, and how to use VBA in Access to control and enhance other Office applications. What you will learn from this book How to take advantage of the built-in Access object library, using Access commands and executing them from any Access toolbar What you need to know to design your own classes, implement common APIs in your code, and use SQL to access data How to configure custom menus for your Access database applications Ways to transfer information between Access and Excel, Word, Outlook®, and other Office programs How to show or hide entire sections of reports based on data entered on a form, or hide form fields based on database login information Object models you can use when writing VBA code in Access, and a list of common API functions to use in your code Who this book is for This book is a comprehensive resource for Access users and VBA developers who want to increase the power of Access using VBA. In addition to experience with VBA, you should have read at least one tutorial covering VBA for Access. Wrox Programmer's References are designed to give the experienced developer straight facts on a new technology, without hype or unnecessary explanations. They deliver hard information with plenty of practical examples to help you apply new tools to your development projects today.